The Relationship of limited-time offers on shopee live with impulse buying among PLM students - Dayrit, Dara Dawn M.; Lao, Angelica Yza Y.; Malang, Reian Mhae M.; Maquirang, Pearl Joy E.; Martinez, Julian Joseph N.; Obenza, Kyla Jemina A.; Valenzuela, Arnie Kyle G.; Vicente, Michael C. 4 0 16; 5
ABSTRACT: This research investigates the relationship between limited-time offers (LTO) and Pamantasan ng Lungsod ng Maynila (PLM) students impulse buying (IB) during Shopee Live. The researchers goal is to fill the underlying gaps and present the findings to consumers and business owners in the most useful way possible. The research uses a quantitative descriptive correlational approach to examine the relationship between LTO and IB among the undergraduates of PLM. Moreover, non-probability convenience sampling was applied to select samples, which had a total of 375 responded to the survey questionnaire adapted from previous studies. It is structured to statistically analyze the relationships between the variables without inferring causality. Findings of this study show that Shopee Live's store factors, including store environment (SE) and friendly employee (FE), have a significant relationship with LTOs with a weak positive correlation coefficient, while sales promotion has strong positive relationship with LTO. Results also indicated that LTOs have a strong positive and significant relationship with the IB of the respondents. These results take psychological comprehension into account, confirming the effect of store factors on LTO and its relationship to IB.
Business Research: (BSBA major Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2